BOOSTING THE ENGLISH VOCABULARIES THROUGH “CUBLAK- CUBLAK SUWENG” FOR YOUNG LEARNERS IN HYBRID CLASSROOM - Daniar Sofeny; Fariq Shiddiq Tasaufy; Annis Rahmawati (PROJECT (Professional Journal of English Education), 2024)
The digital era brings young learners play technology based online games more than the traditional games. Whereas, they contain many individual and passive elements. The purposes of this research were to know the implementation of “Cublak-cublak Suweng” as modified traditional game in increasing the English vocabularies of young learners in hybrid classroom. The second, to know the students’ perception in playing Cublak-cublak Suweng in their classroom. The research used descriptive qualitative method with purposive sampling. Thirty elementary school students participated in the research. The research used tests, interviews, observation, and documentations for data collection techniques. The result showed that “Cublak-cublak Suweng” as modified traditional game gave a positive impacts on learning and boosting students’ vocabularies of English. It was seen from 72% of students having a ‘very good  and  excellent” level. In the score range of 80-90. Second, the perception of students stated that “Cublak-cublak Suweng” is  effective learning strategy in English vocabularies classroom. So, “Cublak-cublak Suweng” is effective to use in boosting the English vocabularies of young learners in hybrid classroom.